Calcul the sum is a very interesting subject, so I present to you this one. Can you solve it ?:D

Prove that: \(\forall{n}\in{N}\), \(\displaystyle \sum_{i+j=n}C^i_n(i+1)^{i-1}(j+1)^{j-1}=2(n+2)^{n-1}\).

Calcul the sum is a very interesting subject, so I present to you this one. Can you solve it ?:D

Prove that: \(\forall{n}\in{N}\), \(\displaystyle \sum_{i+j=n}C^i_n(i+1)^{i-1}(j+1)^{j-1}=2(n+2)^{n-1}\).

No vote yet

4 votes

×

Problem Loading...

Note Loading...

Set Loading...

## Comments

Sort by:

TopNewestgo with pmi i.e principal of mathematical induction – Gagan Maheshwari · 3 years, 7 months ago

Log in to reply

– Quan Dinh · 3 years, 7 months ago

Can you write it down more clearly? Thanks!Log in to reply